Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1093/hmg/ddv330
|View full text |Cite
|
Sign up to set email alerts
|

Glial TDP-43 regulates axon wrapping, GluRIIA clustering and fly motility by autonomous and non-autonomous mechanisms

Abstract: Alterations in the glial function of TDP-43 are becoming increasingly associated with the neurological symptoms observed in Amyotrophic Lateral Sclerosis (ALS), however, the physiological role of this protein in the glia or the mechanisms that may lead to neurodegeneration are unknown. To address these issues, we modulated the expression levels of TDP-43 in the Drosophila glia and found that the protein was required to regulate the subcellular wrapping of motoneuron axons, promote synaptic growth and the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 32 publications
(39 reference statements)
7
25
0
Order By: Relevance
“…In this respect, we have reported that the endogenous TDP-43 (TBPH) is localized in glial cells in Drosophila melanogaster, where it prevents motoneuron degeneration. This supports the idea that ALS may have a nonneuronal origin [11]. In consonance with this hypothesis, pathological modifications of TDP-43 have been found in the skeletal muscles of patients with different neuromuscular diseases such as inclusion body myositis (IBM) and sporadic, familial forms of ALS [12].…”
Section: Introductionsupporting
confidence: 76%
“…In this respect, we have reported that the endogenous TDP-43 (TBPH) is localized in glial cells in Drosophila melanogaster, where it prevents motoneuron degeneration. This supports the idea that ALS may have a nonneuronal origin [11]. In consonance with this hypothesis, pathological modifications of TDP-43 have been found in the skeletal muscles of patients with different neuromuscular diseases such as inclusion body myositis (IBM) and sporadic, familial forms of ALS [12].…”
Section: Introductionsupporting
confidence: 76%
“…In this direction, the critical role of the glia and immune cells in the progression of the disease has been recently described in ALS individuals and confirmed in different animal models (Boillée et al, 2006;Brettschneider et al, 2012;Diaper et al, 2013;Ince et al, 2011;Tong et al, 2013). Regarding to that, we have reported that the endogenous TDP-43 protein in Drosophila melanogaster (TBPH) localizes in glial cells and is required in these tissues to prevent motoneurons degeneration supporting the idea that ALS may present a non-neuronal origin [10]. In consonance with this hypothesis, pathological modifications in TDP-43 were also detected in the skeletal muscles of patients suffering of different neuromuscular diseases alike inclusion body myositis (IBM) or sporadic and familial forms of ALS [12].…”
supporting
confidence: 71%
“…In transgenic rats with restricted neuronal expression of an ALS-linked mutant TDP-43 or FUS, lipocalin-2 is upregulated in reactive astrocytes and may have a direct neurotoxic effect [85]. Likely, glial and neuronal cells respond in a different manner to the toxic accumulation of TDP-43, but a growing body of evidence suggests an important role of TDP-43 dysfunction in astrocytes in the context of motor neuron degeneration in ALS [45, 8688]. Interestingly, TDP-43 is present in the eosinophilic inclusions characteristically found within astrocytes in the brain of Alexander disease patients [89], suggesting that primary alteration of TDP-43 biology within astrocytes can lead to neurodegeneration.…”
Section: Astrocyte-mediated Motor Neuron Toxicitymentioning
confidence: 99%